Avaliação da toxicidade do extrato aquoso de Scutia buxifolia em ratos - Freitas, Robson Borba de (2013)
Medicinal plants were and are very important for healing various diseases. However, improper use of plants for therapeutic purposes can cause a number of side effects. There are in the literature various reports about plants induced-toxicity and, in some cases patients have hepatic disorders. The knowledge about toxicity of vegetable materials is insipient because there are few scientific studies related to pharmacokinetics and pharmacodynamics. Plants containing pyrrolizidine alkaloids show hepatotoxic effects well documented. Scutia buxifolia Reiss is a Rhamnaceae. This plant occurred in Uruguay, Argentina and Brazil. It is used for hypertension treatment. Extracts and fractions obtained from S. buxfolia have antimicrobial and antioxidants effects. Nevertheless, S. buxifolia toxic effects are unknown. The present study was aimed to evaluate the acute and sub-chronic toxicity of S. buxifolia aqueous extract (SBSB). The flavonoids, condensed tannins, and flavonoids were measured in SBSB. The antioxidant scavenger capacity of SBSB was determined by DPPH assay. Antioxidant power of SBSB was comparable with the antioxidant ascorbic acid. The single dose of SBSB at concentrations 100, 200, 400 mg/ kg body weight administered to Wistar rats did not cause mortality and, behavioral changes. Then, we speculate that the lethal dose of SBSB is greater than 400 mg / kg body weight. In the sub-chronic assay, thirty-two animals are divides in 4 groups: the control group which receive distilled water by gavage and, the experimental groups which received the same doses used in the acute toxicity assay. The animals received water or SBSB once a day, during 30 days. The serum alanine aminotransferase (ALT) and asparate aminotransferase (AST) activities and, serum albumin levels were measured on 15º and 30º day of treatment. The malondialdehyde (MDA) and non-protein thiol groups (NPSH) contents and, the antioxidant activities of superoxide dismutase (SOD) and catalase (CAT) were quantified in the liver. Treatment with SBSB did not elevate the activity of AST and ALT, and did not alter the level of serum albumin in the doses of 100 and 400 mg / kg body weight. In animals treated with 200 mg / kg an increased activity of the enzyme AST was observed. This fact can occurred due, probably, to hemolysis. Treatment with SBSB preserves antioxidant defenses and does not increase the lipid peroxidation in liver tissue. These findings along with histopathological analysis show that the SBSB is safe.